b) Do a;b;c` là 3 số hạng liên tiếp của cấp số cộng nên:
`2b = a + c`
Ta có:
`VT = 2(a+b+c)^3 = 2 . (3b)^3 = 2 . 27 . b^3 = 54b^3`
`VP = 9 [a^2 (b+c) + b^2 (a+c) + c^2 (a+b)]`
`= 9 (a^2 b + a^2 c + b^2 . 2b + c^2 a+ c^2 b)`
`= 9 (a^2 b + a^2 c + 2b^3 + c^2 a+ c^2 b)`
`= 9 ((a^2 b+ c^2 b) + (a^2 c+ c^2 a) + 2b^3 )`
`= 9 (b(a^2 + c^2) + ac(a + c) + 2b^3 )`
`= 9 (b(a^2 + c^2 + 2ac) + 2b^3 )`
`= 9 (b(a+c)^2 + 2b^3 )`
`= 9 (b. (2b)^2 + 2b^3 )`
`= 9 (4b^3 + 2b^3 )`
`= 9 . 6b^3`
`= 54b^3`
Nên `VT = VP (đpcm)`
a) Do ` a;b;c` là 3 số hạng liên tiếp của cấp số cộng nên:
`2b = a+ c`
Khi đó:
`VT = a^2 + 2bc = a^2 + (a+c).c = a^2 + ac + c^2 = a(a+c) + c^2 = c^2 + 2ab = VP (đpcm)`